“The Graying Minority”: Lived Experiences and Psychosocial Challenges of Older Transgender Adults During the COVID-19 Pandemic in India, A Qualitative Exploration - Banerjee, Debanjan; Rao, T. S. Sathyanarayana (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic has emerged as a global health threat. Certain factors like age, immunocompromised state, social impoverishment, etc. can add to the vulnerabilities during this pandemic. One such group are the older transgender adults, who often bear a combination of these risks. As the world is ageing fast, their numbers have also been increasing. Keeping this in the background, this study explores the lived experiences and psychosocial challenges of the older transgender adults during the COVID-19 pandemic in India. Methods: 10 individuals with ‘transgender’ identity above 60 years of age were recruited with consent through purposive sampling. Telephonic in-depth interviews were conducted using a pre-designed interview schedule. They were recorded, translated and transcribed verbatim. Hasse’s adaptation of Colaizzi’s phenomenological method was used for analysis. Independent coding and respondent validation were used to establish the data rigor. Results: The predominant categories (with themes) were marginalization (‘second’ priority, stigma, social disconnection), the dual burden of ‘age’ and ‘gender’ (ageism, othering and psychosexual difficulties) and multi-faceted survival threats (physical, emotional, financial) during the pandemic. Social rituals, spirituality, hope and acceptance of ‘gender dissonance’ emerged as the main coping factors, whereas their unmet needs were that of social inclusion, awareness related to COVID-19, mental health care and audience to their distress. Conclusion: The elderly gender minorities are at increased emotional and social risks during the ongoing pandemic, and their voices are mostly unheard. Need for policy implementation and community awareness about their social welfare are vital to improve their health and wellbeing.